1997
DOI: 10.1002/bjs.1800840417
|View full text |Cite
|
Sign up to set email alerts
|

Surgical care and outcome for patients in their nineties

Abstract: Very elderly patients can be managed with a reasonable expectation of good outcome after admission for surgical care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
5
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 9 publications
3
5
0
Order By: Relevance
“…In the study by Arenal and colleagues, the patients over-90 years with colorectal cancer who underwent urgent surgery accounted for 49% of the sample [16]. These data are similar to other reports [17, 18, 19, 20]. The possible explanation for this recurrent urgent presentation in nonagenarian patients is that the diagnosis was frequently triggered by a complication manifestation.…”
Section: Discussionsupporting
confidence: 74%
“…In the study by Arenal and colleagues, the patients over-90 years with colorectal cancer who underwent urgent surgery accounted for 49% of the sample [16]. These data are similar to other reports [17, 18, 19, 20]. The possible explanation for this recurrent urgent presentation in nonagenarian patients is that the diagnosis was frequently triggered by a complication manifestation.…”
Section: Discussionsupporting
confidence: 74%
“…The oldest patients with few comorbid conditions and nonemergency operations have outcomes comparable to younger age groups. 108 Studies [109][110][111] from the National Veterans Affairs Surgical Quality Improvement Program database have demonstrated that age, as an independent variable, is less important in predicting postoperative outcome than complexity scores, functional status, emergency nature of cases, or the preoperative anesthesia risk assessment scores. Still, the rate of surgical complications consistently increased with age, with 3 to 4 times as many of the oldest patients having more than one complication ( Table 4).…”
Section: Surgical and Perioperative Complicationsmentioning
confidence: 99%
“…Cancer is common in nonagenarians. From surgical and oncological points of view this age group is not well understood, there being few reports concerning the impact of surgery in nonagenarians [1–12]. Cancer in these elderly patients presents an ethical dilemma for surgeons and oncologists as to how aggressive an approach should be taken when it comes to treating cancer, balancing the increased risks associated with surgery against the patient’s relatively short life expectancy.…”
Section: Introductionmentioning
confidence: 99%